IDENTIFICATION OF PERMABLE ZONE IN KAMOJANG â GUNTUR GEOTHERMAL FIELD BASED ON DIELECTRIC PERMITTIVITY AND MAGNETIC PERMEABILITY DERIVED FROM SAR POLARIMETRIC - Ilham Fathoni, Muhammad
The Permeable Zone has a vital role in a geothermal system and is one factor that controls the emergence of geothermal manifestations on the surface. This zone is associated with faults and fractures that allow thermal fluid to flow from the reservoir to the surface. This study aims to identify permeable zones based on physical parameters such as relative dielectric permittivity (?r) and relative magnetic permeability (?r) derived from Advanced Land Observing Satellite 2 Phased Array type L-Band Synthetic Aperture Radar 2 (ALOS 2 PALSAR 2) image. The ALOS-2 PALSAR-2 image is corrected through a multi-looking and terrain correction process to obtain optimal image focus and provide planimetric coordinates to the image. Parameters of relative dielectric permittivity (?r) and relative magnetic permeability (?r) were obtained using the magnetic and dielectric method from Polarimetric Synthetic Aperture Radar (mdPSAR). Direct measurements in the field are also carried out using the Ferromaster Magnetic Permeability Meter instrument. The results of the mdPSAR method are then verified by calculating the linear regression value and the distribution of residual values between the mdPSAR parameters and the field parameters. Verification of the mdPSAR results that have been carried out obtains a coefficient of determination of 0.82 with a normal residual distribution, which indicates the results of this method have a good correlation with the in-situ measurement data. In-situ measurement data and mdpSAR parameters show anomaly low ?r and high ?r values in the permeable zone. Seven zones were identified at the research site which have permeable zone characteristics based on the mdPSAR physical parameters. The seven zones consist of four manifestation zones (Kamojang Crater, Guntur Crater, Masigit, and Tarogong) and three nonmanifest zones (Gajah, Gandapura, and Danau Pangkalan).